Serotype distribution of invasive, noninvasive and carried Streptococcus pneumoniae in Malaysia: a meta-analysis - Lister, Alex J. J.; Le, Cheng Foh; Cheah, Eddy Seong Guan; Mohd Desa, Mohd Nasir; Cleary, David W.; Clarke, Stuart C. (BioMed Central, 2021)
Background: Pneumococcal pneumonia is the leading cause of under-five mortality globally. The surveillance of pneumococcal serotypes is therefore vital for informing pneumococcal vaccination policy and programmes. Pneumococcal conjugate vaccines (PCVs) have been available as an option in the private healthcare setting and beginning December 2020, PCV10 was incorporated as part of routine national immunisation programme (NIP) in Malaysia. We searched existing literature on pneumococcal serotype distribution across Malaysia to provide an overall view of this distribution before the implementation of PCV10. Methods: Online databases (PubMed, Ovid MEDLINE and Scopus), reference lists of articles identified, and grey literature (Malaysian Ministry of Health website, WHO website) were systematically searched for relevant literature on pneumococcal serotype distribution across Malaysia up to 10th November 2020. No lower date limit was set to maximise the number of target reports returned. Results of serotypes were split by age categories, including ≤5 years, > 5 years and unreported for those that did not specify. Results: The search returned 18 relevant results, with a total of 2040 isolates. The most common serotypes across all disease types were 19F (n = 313, 15.3% [95%CI: 13.8–17.0]), 23F (n = 166, 8.1% [95%CI: 7.0–9.4]), 14 (n = 166, 8.1% [95%CI: 7.0–9.4]), 6B (n = 163, 8.0% [95%CI: 6.9–9.2]) and 19A (n = 138, 6.8% [95%CI: 5.8–7.9]). Conclusion: Four of the most common serotypes across all isolate sources in Malaysia are covered by PCV10, while PCV13 provides greater serotype coverage in comparison to PCV10. There is still a need for surveillance studies, particularly those investigating serotypes in children under 5 years of age, to monitor vaccine effectiveness and pneumococcal population dynamic following implementation of PCV10 into routine immunisation.